KArAT (Knee Arthroplasty Activity Trial): Rationale and design features of a multicenter randomized controlled trial - Elena Losina; Jamie E. Collins; Mahima Kumara; Linda Ehrlich-Jones; Maame Opare-Addo; Clare Safran-Norton; Neil A. Segal; Lauren M. Mitchell; Paul T. Kopp; Faith Selzer; Hanna Mass; Michael Paskewicz; et al. (Osteoarthritis and Cartilage Open)
Background: Total knee arthroplasty (TKA) is commonly performed to relieve pain in persons with severe knee osteoarthritis. Despite substantial pain reduction and functional improvements, physical activity (PA) does not necessarily increase post TKA. The premise for this randomized trial is that a behavioral intervention invoking internal and external motivators could lead to improvement in PA uptake post TKA. Methods: KArAT (the Knee Arthroplasty Activity Trial) is a three-arm multi-center randomized controlled trial designed to establish the efficacy and sustainability of a personalized behavioral intervention in improving PA among TKA recipients with a primary diagnosis of knee osteoarthritis. The three arms include: 1) usual care, 2) attention control with Fitbit activity trackers, and 3) health coaching and financial incentives for reaching personalized PA goals. The primary outcome is defined as the proportion of participants engaged in at least 150 ​min of moderate-to-vigorous physical activity over a given week after the 6-month intervention. We also plan to conduct a cost-effectiveness analysis to establish the value and affordability of the KArAT interventions. Discussion: This paper aims to outline the rationale, study design, and implementation of KArAT. Trial Registration: Clinicaltrials.gov NCT04107649.